2001
DOI: 10.1007/s007010170062
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemangiopericytoma: Study of 12 Cases

Abstract: Most hemangiopericytomas (HPCs) are located in the musculoskeletal system and the skin, while the intracranial location is rare. They represent 2 to 4% in large series of meningeal tumours, thus accounting for less than 1% of all intracranial tumours. Many authors have argued about the true origin of this tumour. The current World Health Organization classification of Central Nervous System tumours distinguishes HPC as an entity of its own, and classified it into the group of "mesenchymal, non-meningothelial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 45 publications
7
82
3
Order By: Relevance
“…They are found mostly at supratentorial, less frequently at infratentorial, very rarely intraventricular and even intraparenchymal locations have been reported (Muttaqin et al, 1991;Abrahams et al, 1999;Alen et al, 2001;Kuzeyli et al, 2003). Similarly, most of MHPC as well as MNG in our cases are in a supratentorial location.…”
Section: Discussionsupporting
confidence: 62%
“…They are found mostly at supratentorial, less frequently at infratentorial, very rarely intraventricular and even intraparenchymal locations have been reported (Muttaqin et al, 1991;Abrahams et al, 1999;Alen et al, 2001;Kuzeyli et al, 2003). Similarly, most of MHPC as well as MNG in our cases are in a supratentorial location.…”
Section: Discussionsupporting
confidence: 62%
“…This finding contrasted with other studies in which calcification was not seen in hemangiopericytoma. 2,4 Calcification in meningeal hemangiopericytoma has rarely been reported; indeed, we could find only 4 cases in 3 studies [12][13][14] : a 67-year-old woman, a 23-year-old woman, a 6-week-old boy, and a 12-year-old girl. Calcifications in these 5 cases (including the patient in our study) were all located in the tumor periphery.…”
Section: Discussionmentioning
confidence: 79%
“…However, the lesion was large and primary radiotherapy was not considered to be a suitable option. 1,6) The radiological features suggested that the lesion was located in the intracavernous sinus. During surgery the lesion was found within the dural confines of the lateral wall of the cavernous sinus.…”
Section: Discussionmentioning
confidence: 99%